2011
DOI: 10.1152/ajpregu.00659.2010
|View full text |Cite
|
Sign up to set email alerts
|

Low intrinsic running capacity is associated with reduced skeletal muscle substrate oxidation and lower mitochondrial content in white skeletal muscle

Abstract: Chronic metabolic diseases develop from the complex interaction of environmental and genetic factors, although the extent to which each contributes to these disorders is unknown. Here, we test the hypothesis that artificial selection for low intrinsic aerobic running capacity is associated with reduced skeletal muscle metabolism and impaired metabolic health. Rat models for low- (LCR) and high- (HCR) intrinsic running capacity were derived from genetically heterogeneous N:NIH stock for 20 generations. Artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 56 publications
8
50
0
Order By: Relevance
“…The present study used female rats from generations 16,20, and 22, as the body weight differences between phenotypes are less marked in females than in males at the same age (16), and hence body weight is less likely to represent a confounding influence to our observations. Rats were phenotyped for intrinsic running capacity at 11 wk of age (26,43,49) and were studied in two age groups, young (ϳ12 wk) and mature adulthood (ϳ35 wk). Conscious fasting glucose tolerance tests were determined (26,43,49) Tissue collection and histology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study used female rats from generations 16,20, and 22, as the body weight differences between phenotypes are less marked in females than in males at the same age (16), and hence body weight is less likely to represent a confounding influence to our observations. Rats were phenotyped for intrinsic running capacity at 11 wk of age (26,43,49) and were studied in two age groups, young (ϳ12 wk) and mature adulthood (ϳ35 wk). Conscious fasting glucose tolerance tests were determined (26,43,49) Tissue collection and histology.…”
Section: Methodsmentioning
confidence: 99%
“…Rats were selectively bred to yield divergent phenotypes with either low (LCR) or high (HCR) intrinsic running capacity. When compared with HCR, LCR rats have reduced whole body insulin sensitivity, glucose tolerance, and hyperlipidemia, indicative of poor metabolic health (26,43,46,49). Furthermore, LCR rats exhibit modest but significantly higher systolic blood pressure (SBP) compared with HCR, particularly in males (6, 49).…”
mentioning
confidence: 99%
“…Furthermore, LCRs have increased cardiovascular disease risk and higher susceptibility to tachyarrhythmia's than HCRs . Previous studies have also shown that LCRs have poor capillarization, less subsarcolemmal and intermyofibrillar mitochondria, and reduced mitochondrial respiratory capacity in skeletal muscle compared to HCRs (Kivelä et al 2010;Rivas et al 2011;Walsh et al 2006). In liver tissue, LCRs exhibit reduced hepatic mitochondrial oxidative capacity that in turn increases susceptibility to hepatic steatosis and liver injury (Thyfault et al 2009).…”
Section: Hcr/lcr Rat Model Systemmentioning
confidence: 99%
“…The larger contractile-mediated decrease in pH in the triceps surae of LCRs was likely related to the larger glycolytic ca-pacity in fast-twitch muscle fibers (type 2b) of LCRs compared to HCRs (Termin, Staron & Pette 1989;Fuchtbauer et al 1991;Kivelä et al 2010). Additionally, HCRs may have more efficient hydrogen ion buffering and a delayed decline in Ca 2+ release due to higher oxidative capacity in skeletal muscle (Kivelä et al 2010;Rivas et al 2011), which might help resist fatigue.…”
Section: Skeletal Muscle Propertiesmentioning
confidence: 99%
See 1 more Smart Citation